Peer Group Dynamics and Juvenile Delinquency: Building Positive Habits through Peer Influence - Dany Mifath M. Nur; Tasya Lutfiana Rahmasari; Ahmad Eko Setiyawan (JURNAL PENDIDIKAN IPS, 2024)
Teenagers are influenced by the environment and peers. These group dynamics are important in shaping adolescent behavior, especially delinquency. This research explores the relationship between peer group dynamics and juvenile delinquency, as well as the potential positive influence of peers in forming good habits. This study examines social, psychological, and environmental factors in peer group dynamics that influence juvenile delinquent behavior. Factors such as peer pressure, group identity, and social conformity are analyzed to understand their influence on adolescents' detrimental behavior. However, this research also highlights the positive role of peer groups in forming positive habits. With the right approach, peers can become agents of change who influence teenagers in adopting habits that support healthy development. Educational strategies, such as strengthening social skills, understanding the consequences of behavior, and a supportive environment, can direct peer influence in a positive direction. This research provides a comprehensive view of the role of peer group dynamics in shaping adolescent behavior, both delinquency and positive habits. The implications of this research emphasize the important role of parents, schools, and communities in forming an environment that supports and guides peer influence for a positive impact on adolescent development.